Accounting Conservatism: A Review of Literature - Soyemi, Kenny Adedapo; Akingunola, Richard Ore-Oluwa; Olaniyan, Joshua (NIU Journal of Social Sciences; Vol 4 No 3 (2018): KIU Journal of Social Sciences, Vol. 4 No. 3, September 2018, 2018)
Conservatism is one of the most controversial principles in financial reporting giving the conflicting perspectives of users of financial information on its effect. This study therefore reviews the conceptualization, operationalization, and empirical findings on accounting conservatism. We conclude that accounting conservatism cannot be totally eliminated from financial reporting. However, stakeholders and users of financial reporting may need to reach a compromise on the level at which conservatism may be practiced. Furthermore, we conclude that perspectives on conservatism on financial reporting cannot be generalised giving other social-economic variables which are peculiar to a reporting entity. Finally, we recommend that African countries may need to corroborate or refute findings emanating from the developed economy on accounting conservatism. Keywords : Accruals, Conservatism, Financial reporting, Financial Statements, Management